Malignancy after Pediatric Kidney Transplantation: The 30-Year Experience of a Single Center - Jiwon Jung; Young Seo Park; Duck Jong Han (Korean Society of Pediatric Nephrology, 2020)
Objectives We aimed to investigate the incidence, manifestations, and outcomes of malignancy after pediatric kidney transplantation (KT) at our center over 30 years. Methods We retrospectively reviewed the medical records of 155 patients under 18 years of age who underwent KT between January 1990 and February 2020 at Asan Medical Center. Results Twelve patients (7.7%) were diagnosed with a malignancy after KT. Malignancy was diagnosed after a mean period of 6.4±5.9 years (median 4.6, range 0.5-20.6 years) after KT. Nine (75.0%) of the 12 cancer patients were diagnosed with post-transplant lymphoproliferative disease (PTLD), and the other three had papillary thyroid cancer, mucoepidermoid cancer of the hard palate, and T-cell acute lymphoblastic leukemia, respectively. PTLD was diagnosed within a mean of 3.7±3.4 years (median 3.7, range 0.5-9.8 years) after KT. Five patients diagnosed with PTLD were cured without recurrence. Three patients with PTLD died from the disease, and one patient with mucoepidermoid cancer from a non-PTLD malignancy died after progression, despite surgical resection and chemotherapy. Three (33.3%) of the nine survivors progressed to end-stage renal disease (ESRD) after completing cancer treatment. No patient with post-transplant malignancy (PTM) experienced critical renal deterioration during cancer treatment. Conclusion PTLD was the most common PTM, occurring at 5.8% of the pediatric KT patients after KT in our center. Careful follow up is needed particularly considering the risk of PTLD after KT in children.